Small angle neutron scattering from anisotropic micelles aligned by shear flow - Penfold, J; Staples, E; Cummins, P (Publ by ACS, 1990)
Shear flow is now an established technique for aligning anisotropically shaped micelles in small angle neutron scattering (SANS) studies. In an earlier paper we have described the changes in micelle geometry that occur for hexaethyleneglycol monohexadecylether (C16E6) in the vicinity of its lower consolute boundary. This work has been extended to the study of C16E6 in the presence of 'salting in' electrolyte: the additional of electrolyte elevates the cloud curve such that the evolution of micelle size can be followed over a wider temperature change. Small angle neutron scattering measurements have been made on the D11 and on the LOQ spectrometer. The addition of 'salting in' electrolyte (sodium thiocyanate. NaSCN) to C16E6 has an effect on all regions of the phase diagram consistent with the ethylene oxide (EO) chain length being effectively increased. We now have clear evidence of the relative importance of the contributions of the coulombic intermicellar interactions, shear forces and the temperature dependent EO-EO interactions to the stability and geometry of these systems.